Double-ionization satellites in the K-VV Auger spectra of neon-like molecules; Journal of Physics B: Atomic, Molecular and Optical Physics; Vol. 32, № 4 - Novikov S. A. Sergey Avtonomovich (1999, 1999)
The processes of monopole double ionization are investigated in the K-VV Auger spectra of the neon-like molecules (HF, H2O, NH3 , CH4). The spectra are calculated with simultaneous inclusion of multiplet splitting, final-state mixing and contributions of the ligands atomic orbitals to the molecular Auger transition amplitudes. The calculated relative integral intensities of the shake-off and shake-up spectator satellites are 18.2-20.5% of the total intensities of molecular Auger spectra. Taking the shake satellites into account allows us to assign some features of molecular Auger spectra.